Access to unsymmetrically substituted diaryl Gold N-Acyclic Carbene (NAC) and N-Heterocyclic Carbene (NHC) complexes via the isonitrile route - Vethacke, Vanessa; Claus, Vanessa; Dietl, Martin C.; Ehjeij, Daniel; Meister, Arne; Huber, Jonas F.; Paschai Darian, Leon K.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2022)
A variety of unsymmetric diaryl gold N-acyclic carbene (NAC) complexes was synthesized via the isonitrile route by three different methods: (a) solvent free in a melt, (b) mechanochemically and (c) in THF at room temperature. The latter method can also be used to synthesize unsaturated gold NHC complexes. These methods overall offer access to a broad array of new complexes and remove one of the previous limitations of the isonitrile route to NAC and NHC complexes of gold, namely the inability to react with the less nucleophilic aromatic amines. The new complexes also proved to be successful as pre-catalysts in the gold-catalyzed phenol synthesis.